Day 3 Wed, August 07, 2019 2019
DOI: 10.2118/198789-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Macroscopic Displacement Efficiency of Locally Sourced Locust Bean Gum and Gum Arabic

Abstract: In enhancing oil recovery through polymer flooding, the application of polymers have been basically structured around the use of commercial polymers like xanthan gum, scleroglucan, Hydroxyl ethyl cellulose, Polyacrylamide, Hydrolysed Polyacrylamide and its derivatives. The use of some of these polymer has led to negative environmental issues and also increased treatment cost prior to discharge. The cost of some of the polymers is another reason, their applicability have not been appreciated so much in the oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Modelling and Simulation in Engineering gum Arabic flooding using sandpacks achieved incremental recovery of 26% of OOIP and total recovery of 80% [34]. Xanthan gum and guar gum achieved a total recovery of 63 and 53%, respectively, while gum Arabic achieved 52% for the highest percentages of the three polymer used (0.5% xanthan, 0.5% guar, and 1.0% gum Arabic).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Modelling and Simulation in Engineering gum Arabic flooding using sandpacks achieved incremental recovery of 26% of OOIP and total recovery of 80% [34]. Xanthan gum and guar gum achieved a total recovery of 63 and 53%, respectively, while gum Arabic achieved 52% for the highest percentages of the three polymer used (0.5% xanthan, 0.5% guar, and 1.0% gum Arabic).…”
Section: Resultsmentioning
confidence: 95%
“…In total, xanthan gum produced a total recovery of 63%. Some studies in the literature have shown xanthan gum to produce incremental recovery between 9 and 18% and total recovery of up to 80% [19,20,34].…”
Section: Resultsmentioning
confidence: 99%